Measuring the efficiency of colleges at the University of Al-Qadisiyah-Iraq : a data envelopment analysis approach - Drebee, Hayder Abbas; Nor Azam Abdul Razak (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aims at measuring the efficiency of the colleges at University of Al-Qadisiyah for the academic year 2015- 2016. Data Envelopment Analysis (DEA) was employed with alternative models, namely, CRS-I, CRS-O, VRS-I, and VRS-O. The number of enrolled students, lecturers, employees, and teaching assistants were used as inputs, while the number of students with bachelor’s degree and published research in national and international journals were used as outputs. The results indicate that 58% of the colleges reached their optimum economic size according to the efficiency scale since these colleges reached full efficiency. The college of Nursing is a peer college for inefficient colleges. To achieve full efficiency, there must be either significant reductions in their inputs with the same amount of output (input oriented) or significant increases in output retaining the current amount of inputs (output oriented). In general, the efficiency score of University of Al-Qadisiyah indicated the possibility of reducing its available resources by 10% retaining the current amount of output to be efficient, or expanding the University’s output by 1% retaining the current amount of inputs. Therefore, it is imperative that the decision makers at the University of Al-Qadisiyah and its colleges that have not achieved the required efficiency examine the factors that have contributed to this outcome in order to acquire knowledge of weaknesses and imbalances in their inputs and outputs. They could exploit the available resources efficiently by comparing their inputs and outputs with those of peer colleges.